The Position of Women in the Military: Ethnic Tamil Female Combatants in the Liberation Tigers of Tamil Eelam (LTTE) (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2020)
This paper discusses various factors behind the ethnic Tamil women who decided to join the terrorist militia group, Liberation Tigers of Tamil Eelam (LTTE), in the northern and southeastern parts of Sri Lanka. In this discussion it is known that there are three factors that affect the decision of Tamil women ​​to join the LTTE, namely: first, the existence of the Tamil community as an ethnic minority. Second, the occurrence of mass sexual violence and abuse among Tamil women, perpetuated by the Sri Lanka’s majority ethnic group. Finally, the decision of Tamil women to join LTTE is due to the pressure that structurally and culturally appears in communities in conflictual areas. Through these three factors, Tamil women ​​then chose to leave their comfort zone and reconstructed their identity by joining the LTTE terrorist militia group. In this case, the involvement of female LTTE combatants in Sri Lanka is not only an attempt to eradicate negative views regarding femininity through military activities, but also a symbol of successful self-liberalization from the practice of gender oppression in conflict situations